Enhancing phosphate availability and growth of C. asiatica in andisols through phosphate-solubilizing bacteria application - Betty Natalie Fitriatin; Andriana Kartikawati; Tualar Simarmata; Emma Trinurani Sofyan (Jurusan Agroteknologi, 2023)
Centella asiatica is a medicinal plant containing asiaticoside bioactive, this is considerably higher if grown in the highlands generally on Andisols. Conversely, phosphorus was deficient in Andisol soils. The experiment aimed to study effect of phosphate solubilizing bacteria (PSB) isolates from the rhizosphere of C. asiatica which can dissolve P, produce plant growth promoters, increase growth of C. asiatica and fertilization efficiency. The research was done at Soil Biology Laboratory, Agriculture Faculty, Universitas Padjadjaran and at the experimental field of Agricultural Technology Research and Assessment Installation Manoko, Lembang District, West Java, Indonesia. The research used a factorial randomized block design with three replications and two factors. The first factor were application techniques: control, root soaking, and soil watering. The second factor were dose of NPK fertilizer and soil conditioner: control, P fertilizer dose of 100%, soil conditioner, P fertilizer dose 75% + soil conditioner, and P fertilizer dose of 100% + soil conditioner. Three superior isolates were isolated from C. asiatica rhizosphere and have been identified as: Paraburkholderia caribensis strain MNL-133, Paraburkholderia caribensis strain DSM 13236, and Pseudomonas aeruginosa strain K19PSE24. The results showed that the application of PSB combined with a dose of P fertilizer and soil conditioner on C. asiatica affected the soil P available, the number of leaves, the number of stolons and plant dry weight.ABSTRAKPegagan (Centella asiatica) salah satu komoditas tanaman obat yang memiliki kandungan bioaktif asiatikosida. Asiatikosida lebih tinggi jika ditanam di dataran tinggi umumnya ordo Andisols. Defisiensi hara fosfor salah satu kendala budi daya pada tanah Andisol. Penelitian ini bertujuan mengkaji pengaruh bakteri pelarut fosfat (BPF) unggul yang diisolasi dari roofer tanaman pegagan yang mampu melarutkan P dan menghasilkan pemacu pertumbuhan tanaman pengaruhnya terhadap peningkatan pertumbuhan tanaman pegagan dan efisiensi pemupukan. Penelitian dilaksanakan di Laboratorium Biologi Tanah, Fakultas Pertanian UNPAD dan di kebun percobaan Instalasi Penelitian dan Pengkajian Teknologi Pertanian (IP2TP) Manoko, Lembang menggunakan Rancangan Acak Kelompok Faktorial dengan tiga ulangan. Faktor pertama adalah teknik aplikasi BPF: kontrol; perendaman akar; penyiraman pada tanah. Faktor kedua yaitu dosis pupuk NPK dan pembenah tanah, yaitu perlakuan kontrol, pupuk P dosis 100%, pembenah tanah, pupuk P dosis 75% + pembenah tanah, dan pupuk P dosis 100% + pembenah tanah. Isolasi BPF dari rhizosfer pegagan menghasilkan isolat unggul yaitu Paraburkholderia caribensis strain MNL-133, Paraburkholderia caribensis strain DSM 13236, and Pseudomonas aeruginosa strain K19PSE24. Hasil menunjukkan pemberian BPF dikombinasikan dengan dosis pupuk P dan pembenah tanah pada tanaman pegagan memberikan pengaruh terhadap P tersedia, jumlah daun, jumlah stolon, dan berat kering tanaman.